Anti-Corrosive Performance Of Wash Primer Based On Mangrove Tannin. - Kassim, M.Jain; Rahim, Afidah Abdul; Ismail, Mohd Azman (2001)
Aqueous acetone extract from bark of Rhizophora appiculata or locally known as bakau minyak was tested for anti-corrosive properties by incorporating the powdered extract in wash primer formulation.